Influence of consumer preference and government subsidy on prefabricated building developer’s decision-making: a three-stage game model - Han, Yanhu; Wang, Lufan; Kang, Ruyuan (Journal of Civil Engineering and Management, 2023)
Consumer preference and government subsidies are two of the key influencing factors in the decision-making of building developers, which plays a leading role in the development of prefabricated building market. However, the majority of the existing efforts only used empirical research methods to identify the barriers of prefabricated construction, and failed to quantitatively study the interaction mechanism, process, and trends among the influencing factors. To address this knowledge gap, this study aims to analyze and quantify the dynamic and interactive relationships among the three major stakeholders in the prefabricated building industry – the government, building developers, and consumers. A three-stage game model was developed, and an analysis of two numerical simulations was conducted. The results provided equilibrium solutions for the optimal selling price and optimal assembly rate for the building developers, as well as the optimal minimum assembly rate for government subsidy. This study provides a better understanding of the interactive behaviors among the major stakeholders, and offers meaningful insights for policy design and strategic planning for promoting the development of prefabricated buildings.